A β-diketiminate manganese catalyst for alkene hydrosilylation: substrate scope, silicone preparation, and mechanistic insight. Issue 39 (22nd August 2018) - Mukhopadhyay, Tufan K.; Flores, Marco; Groy, Thomas L.; Trovitch, Ryan J.
Abstract : A (BDI)Mn catalyst has been found to hydrosilylate olefins and the observed selectivity can be attributed to alkene insertion. Abstract : The dimeric β-diketiminate manganese hydride compound, [( 2, 6-iPr2Ph BDI)Mn(μ-H)]2, was prepared by treating [( 2, 6-iPr2Ph BDI)Mn(μ-Cl)]2 with NaEt3 BH. This compound was characterized by single crystal X-ray diffraction and found to feature high-spin Mn centres that exhibit strong magnetic coupling by EPR spectroscopy. Once characterized, [( 2, 6-iPr2Ph BDI)Mn(μ-H)]2 was found to mediate the hydrosilylation of a broad scope of alkenes at elevated temperature. Aliphatic alkenes were found to undergo anti-Markovnikov hydrosilylation, while the hydrosilylation of styrenes using [( 2, 6-iPr2Ph BDI)Mn(μ-H)]2 afforded Markovnikov's product. Importantly, this catalyst has also been employed for the cross-linking of industrially-relevant silicones derived from vinyl-terminated poly(dimethylsiloxane) and 1, 2, 4-trivinylcyclohexane with catalyst loadings as low as 0.05 mol%. To gain a mechanistic understanding of [( 2, 6-iPr2Ph BDI)Mn(μ-H)]2 -catalyzed olefin hydrosilylation, 4- tert -butylstyrene was added to [( 2, 6-iPr2Ph BDI)Mn(μ-H)]2 and conversion to the monomeric Mn alkyl complex, ( 2, 6-iPr2Ph BDI)Mn(CH(CH3 )(4- t BuPh)), was observed. Isolation of this secondary alkyl intermediate confirms that olefin insertion into the Mn–H bond dictates the observed regioselectivities. The importance of our mechanistic findings as they relate to recent advances in Mn hydrosilylation catalysis is described herein.